Long-term alcohol consumption in relation to all-cause and cardiovascular mortality among survivors of myocardial infarction: the Health Professionals Follow-up Study - Pai, Jennifer K. (Oxford University Press, 2012)
AIMS: The aim of this study was to examine the association between long-term alcohol consumption, alcohol consumption before and after myocardial infarction (MI), and all-cause and cardiovascular mortality among survivors of MI. METHODS AND RESULTS: The Health Professionals Follow-up Study (HPFS) is a prospective cohort study of 51 529 US male health professionals. From 1986 to 2006, 1818 men were confirmed with incident non-fatal MI. Among MI survivors, 468 deaths were documented during up to 20 years of follow-up. Long-term average alcohol consumption was calculated beginning from the time period immediately before the first MI and updated every 4 years afterward. Cox proportional hazards were used to estimate the multivariable-adjusted hazard ratios (HR) and 95% confidence intervals (CI). Compared with non-drinkers, the multivariable-adjusted HRs for all-cause mortality were 0.78 (95% CI: 0.62–0.97) for 0.1–9.9 g/day, 0.66 (95% CI: 0.51–0.86) for 10.0–29.9 g/day, and 0.87 (95% CI: 0.61–1.25) for ≥30 g/day (P(quadratic)= 0.006). For cardiovascular mortality, the corresponding HRs were 0.74 (95% CI: 0.54–1.02), 0.58 (95% CI: 0.39–0.84), and 0.98 (95% CI: 0.60–1.60), P(quadratic)= 0.003. These findings were consistent when restricted to pre- and post-MI alcohol assessments. In subgroup analyses, moderate alcohol consumption was inversely associated with mortality among men with non-anterior infarcts, and among men with mildly diminished left ventricular function. CONCLUSION: Long-term moderate alcohol consumption is inversely associated with all-cause and cardiovascular mortality among men who survived a first MI. This U-shaped association may be strongest among individuals with less impaired cardiac function after MI and should be examined further.